2019
DOI: 10.1097/md.0000000000016333
|View full text |Cite
|
Sign up to set email alerts
|

Histologic predictors of renal outcome in diabetic nephropathy

Abstract: The prognostic utility of histologic features in patients with diabetic nephropathy (DN) classified according to the Renal Pathology Society (RPS) classification is controversial. Therefore, we aimed to evaluate the relationship between histologic changes and renal outcome in DN patients. We examined the renal outcome at November 30, 2017 of 74 adult patients (median age of 54.6 years, 69% male, 81% diabetes mellitus (DM) type 2, estimated GFR (eGFR) 29.6 mL/min) with biopsy proven DN between 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Yu An et al [ 36 ] studied more than 300 patients with type 2 DKD confirmed by biopsy and found that vascular lesion scores demonstrated no association with renal outcomes. However, a different study demonstrated that the presence of arteriolar hyalinosis and arteriosclerosis were associated with renal replacement therapy (RRT) initiation in univariate analyses, although there was no statistical significance in multivariable analyses [ 37 ]. The original classification of arteriosclerosis in DKD only assessed the most severe arteriosclerosis but did not assess the proportion of the arteries involved.…”
Section: Discussionmentioning
confidence: 99%
“…Yu An et al [ 36 ] studied more than 300 patients with type 2 DKD confirmed by biopsy and found that vascular lesion scores demonstrated no association with renal outcomes. However, a different study demonstrated that the presence of arteriolar hyalinosis and arteriosclerosis were associated with renal replacement therapy (RRT) initiation in univariate analyses, although there was no statistical significance in multivariable analyses [ 37 ]. The original classification of arteriosclerosis in DKD only assessed the most severe arteriosclerosis but did not assess the proportion of the arteries involved.…”
Section: Discussionmentioning
confidence: 99%
“…[H2] Diabetic kidney disease GBM thickening is an early morphological feature of diabetic kidney disease (DKD) followed by mesangial matrix expansion and glomerulosclerosis, accompanied by the development of proteinuria and a progressive decline in kidney function [152][153][154][155] . A 2019 study identified GBM thickness as a predictor of renal survival in patients with DKD 156 .…”
Section: [H1] the Gbm In Glomerular Filtrationmentioning
confidence: 99%
“…Moreover, it was reported that interstitial fibrosis, tubular atrophy and interstitial inflammation, but not glomerular lesions, are significant predictors for renal prognosis in T2D patients with overt proteinuria[15]. In a recent study, interstitial fibrosis and tubular atrophy score, as well as glomerular basement membrane thickness, were independent predictors for renal replacement therapy initiation in T2D patients[16]. Taking into account the results of morphological investigations, the assessment of urinary markers of podocyte and interstitial involvement may provide further information on the development of different CKD phenotypes.…”
Section: Introductionmentioning
confidence: 99%